Uso do hormônio luteinizante recombinante em ciclos de fertilização assistida - Maia, Mônica Canêdo Silva (2015)
Controlled ovarian stimulation has become an integral part of infertility treatment. Treatment options with recombinant gonadotrophins add more to knowledge on folliculogenesis and ovarian steroidogenesis. The role of recombinant luteinizing hormone is controversial undergoing ovarian stimulation and has been widely debated. Objective: To compare the effects of supplementation with recombinant luteinizing hormone (rLH) for controlled ovarian stimulation with recombinant follicle stimulating hormone (rFSH) in a protocol with GnRH-antagonist in cycles of IVF/ICSI. Methods: Case-control study with 113 patients attended at a university center in the city of Goiania, aged between 34-42 years, who were divided into two groups according to an ovarian stimulation scheme: Group I (n= 60): rFSH (control group) and Group II (n= 53): rFSH + rLH (treated group). These groups were comparable for age, BMI, duration of infertility, serum FSH, LH and estradiol. Numbers of oocytes collected and in metaphase II, fertilization rate, embryos rate and rates of chemical and clinical pregnancy were analyzed. Data analysis was conducted using the statistical software BioStat ® 5.3. Differences in proportions were assessed by chi-square test and means by Wilcoxon Mann- Whitney test. P < 0,05 was considered statistically significant. Results: The mean age of patients in Group I was 37.3±2.1 years and Group II 37.9±2.4 years (P > 0.05). The comparability of the other main characteristics (duration of infertility, BMI, FSH, LH and basal estradiol) were also observed between Groups I and II (P > 0.05). There was no significant difference between the two groups regarding: number of oocytes retrieved (Group I= 4.9 ± 2.1, Group II= 5.7 ± 2.6, P= 0.061), number of oocytes in metaphase II (Group I= 3.4 ± 1.6, Group II= 4.0 ± 1.9, P= 0.060), fertilization rate (Group I= 65.3%, Group II= 69.4 %, OR 1.20, 95% CI 0.85-1.70, P= 0.282), embryos rate (Group I= 85.4%, Group II= 88.5%, OR 1.31, 95% CI 0.73-2.36, P= 0.355), rate of chemical pregnancy (Group I= 20.0%, Group II= 24.5%; OR 1.30, 95% CI 0.53-3.16, P= 0.562) and clinical pregnancy rate (Group I= 20.0%, Group II= 22.6%, OR 1.17, 95% CI 0.47-2.89, P= 0.731). Conclusion: In this study it was concluded that supplementation with r-LH showed no benefit with respect to variables during controlled ovarian stimulation with GnRH antagonists.